Implementation of STEAM Gamification in Science Learning: A Systematic Literature Review - Wijayanti, Arfilia; ., Wiyanto; ridlo, Saiful; ., Parmin (Journal of Posthumanism, 2025)
The advancement of science and technology in the 21st century calls for integrated and innovative educational approaches to ensure meaningful learning. STEAM—Science, Technology, Engineering, Arts, and Mathematics—offers an interdisciplinary structure, while gamification effectively rejuvenates science education. This systematic review, covering 2016 to 2024 and guided by PRISMA, examined 21 Scopus and Google Scholar studies. It explored key aspects such as research aims, methodologies, outcomes, levels of education targeted, integration models, and dominant disciplines. Findings revealed five main research designs—experimental, mixed methods, developmental, case studies, and qualitative—all showing positive impacts, with university settings being the most common. Science emerged as the core subject, with other STEAM components embedded contextually. Game elements like goals, badges, points, and leaderboards were prevalent, promoting engagement through challenge and reward dynamics. The study confirms the potential of STEAM gamification in enhancing creativity and critical thinking, particularly in higher education.